Evaluating microfoundations for aggregate price rigidities: Evidence from matched firm-level data on product prices and unit labor cost - Mikael Carlsson; Oskar Nordström Skans (Sveriges Riksbank, 2009)
Using data on product-level prices matched to the producing firm's unit labor cost, we reject the hypothesis of a full and immediate pass-through of marginal cost. Since we focus on idiosyncratic variation, this does not fit the predictions of the Ma'ckowiak and Wiederholt (2009) version of the Rational Inattention Model. Neither do we find that firms react strongly to predictable marginal cost changes, as expected from the Mankiw and Reis (2002) Sticky Information Model. We find that, in line with Staggered Contracts models, firms consider both the current and future expected marginal cost when setting prices with a sum of coeffients cients not significantly different from unity.
Keywords: D80; E30; L16; 330; Price Setting; Business Cycles; Information; Micro Data; Preisrigidität; Mikroökonomische Fundierung; Betriebliche Preispolitik; Lohnstückkosten; Unvollkommene Information; Theorie